Bowel function and quality of life after local excision or total mesorectal excision following chemoradiotherapy for rectal cancer. Issue 1 (5th October 2016) - Pucciarelli, S; Giandomenico, F; De Paoli, A; Gavaruzzi, T; Lotto, L; Mantello, G; Barba, C; Zotti, P; Flora, S; Del Bianco, P
Abstract: Background: Local excision for rectal cancer is expected to offer a better functional outcome than conventional surgery. The aim of the present study was to compare quality of life and bowel function in patients with rectal cancer who underwent either local excision or conventional surgery after chemoradiotherapy. Methods: This was a retrospective multicentre study. Patients who underwent local excision were compared with those who had mesorectal excision. Quality of life and bowel function were investigated using validated questionnaires (European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30, EORTC QLQ-CR29 and Memorial Sloan-Kettering Cancer Center Bowel Function Instrument) at a median follow-up of 49 (range 13–95) months. Further analysis was undertaken of data from patients who underwent local excision alone compared with those requiring subsequent radical surgery. Statistical significance was set at P < 0·010. Results: The mean constipation score was significantly better in the local excision group than in the mesorectal excision group (3·8 (95 per cent c.i. 0·3 to 7·2) versus 19·8 (12·1 to 27·4); P < 0·001). Compared with patients who underwent mesorectal excision, those who had local excision had less sensation of incomplete emptying (mean score 3·7 (3·4 to 4·0) versus 2·8 (2·5 to 3·1); P < 0·001) and second bowel movements within 15 min (mean score 3·6 (3·3 to 3·9) versus 3·0 (2·7 to 3·3); P = 0·006). Patients who underwent local excision alone scored better than those who had mesorectal excision, particularly for bowel function, who, in turn, scored better than patients requiring subsequent radical surgery following local excision. Conclusion: Patients who underwent local excision had a better quality of life and bowel function than those who underwent mesorectal excision. Abstract : Less is more